Lived Religion and Gender in Late Medieval and Early Modern Europe - Katajala-Peltomaa, Sari (Taylor & Francis, 2020)
This study is an exploration of lived religion and gender across the Reformation, from the fourteenth to the eighteenth centuries. Combining conceptual development with empirical history, the authors explore these two topics via themes of power, agency, work, family, sainthood, and witchcraft.